(untitled) (Update Dental College Journal, 2024)
The editorial "From Garden to Gumline: Medicinal Plants Revitalize Modern Dentistry" discusses the growing use of medicinal plants in dental treatments, notably those for periodontal disease. Traditional medicines such as aloe vera, neem, turmeric, green tea, and propolis have been scientifically proven for their antibacterial, anti-inflammatory, and healing capabilities, providing natural alternatives to traditional chemical-based therapies. These plants not only assist to manage gum disease, but they also contribute to overall oral health benefits by minimizing the need for medications and combatting antibiotic resistance. While there are barriers to standardization and additional clinical validation, the editorial emphasizes medicinal plants’ potential to become a cornerstone in dental treatment, providing patients with safer, more holistic, and sustainable solutions. Update Dent. Coll. j: 2024; 14(2):1-2